Diffuse brain connectivity changes in Charcot–Marie–Tooth type 1a patients: a resting‐state functional magnetic resonance imaging study. (20th October 2020) - Pontillo, G.; Tozza, S.; Perillo, T.; Cocozza, S.; Dubbioso, R.; Severi, D.; Iodice, R.; Tedeschi, E.; Elefante, A.; Brunetti, A.; Manganelli, F.; Quarantelli, M.
Abstract : Background and purpose: Changes of brain structure and function have been described in peripheral neuropathies. The aim of our study was to systematically investigate possible modifications of major large‐scale brain networks using resting‐state functional magnetic resonance imaging (RS‐fMRI) in Charcot–Marie–Tooth disease type 1A (CMT1A) patients. Methods: In this cross‐sectional study, 3‐T MRI brain scans were acquired of right‐handed genetically confirmed CMT1A patients and age‐ and sex‐comparable healthy controls. Patients also underwent clinical and electrophysiological examinations assessing neurological impairment. RS‐fMRI data were analysed using a seed‐based approach, with 32 different seeds sampling the main hubs of default mode, sensorimotor, visual, salience (SN), dorsal attention, frontoparietal, language and cerebellar networks. Between‐group differences in terms of functional connectivity (FC) with the explored seeds were tested voxelwise, correcting for local grey matter density to account for possible structural abnormalities, whilst the relationship between FC modifications and neurological impairment was investigated using robust correlation analyses. Results: Eighteen CMT1A patients (34.0 ± 11.4 years; M/F 11/7) were enrolled, along with 20 healthy controls (30.1 ± 10.2 years; M/F 11/9). In the CMT group compared to controls, clusters of increased FC with the visual cortex ( P = 0.001), SN ( P < 6 × 10 −4 ), dorsal attention network ( P < 8 × 10 −5 ) and language network ( P < 7 × 10 –4 ) were found, along with a single cluster of reduced FC with the visual cortex in the left lentiform nucleus ( P = 10 –6 ). A significant correlation emerged between neurophysiological impairment and increased FC with right temporal language areas ( r = 0.655, P = 0.006), along with an association between walking ability and increased FC with the left supramarginal gyrus (SN) ( r = 0.620, P = 0.006). Conclusions: Our data show evidence of diffuse functional reorganization involving multiple large‐scale networks in the CMT1A brain, independent of structural modifications and partially correlating with peripheral nerve damage and functional impairment. Abstract : Evidence was found of diffuse functional reorganization involving multiple large‐scale networks in the Charcot–Marie–Tooth disease type 1A (CMT1A) brain, independent of structural abnormalities and partially correlating with peripheral nerve damage and functional impairment. These results, using CMT1A patients as a possible model to explore brain modifications associated with peripheral nervous system pathology, may shed new light onto central nervous system physiopathology and its role in the development of clinical disability in peripheral neuropathies.